Assault-injured youth in the emergency centres of Khayelitsha, South Africa: Baseline characteristics & opportunities for intervention. Issue 12 (December 2019) - Leeper, Sarah; Lahri, Sa'ad; Myers, Justin; Patel, Mehul; Reddy, Priscilla; Martin, Ian B.K.; van Hoving, Daniël J.
Highlights: Assault-injured patients were predominantly male (80%) and the majority of injuries were caused by stabbing (71%). Seventy-nine percent of patients endorsed alcohol and/or drug use prior to the assault. Differences were not detected between women and men. Assault-injured females were more likely than males to be injured as a result of intimate partner violence (26% vs. <1%, p < 0.0001). Many of the risk factors we identified for assault injury parallel trends seen in similar studies in the US, and in other LMICs. Abstract: Introduction: Violence is a leading cause of death worldwide for youth age 15–29. A growing body of literature has described assault-injured youth in United States emergency centres, identifying risk factors for re-injury and mortality, and developing targeted interventions. Despite the fact that low- and middle-income countries are disproportionately affected by violence, little research on assault-injured youth exists in these settings. Methods: Survey and chart review of 14 to 24-year-old assault-injured patients and non-assault-injured controls to 24-hour emergency centres in Khayelitsha, South Africa over 15 weeks. Patient enrollment occurred 7pm Friday to 7am Monday. Multivariable logistic regression was used to estimate associations of behavioral and other factors with assault injury. Results: In total 513 patients were enrolled: 324 assault-injured patients and 189 controls (131 medical, 58 unintentional injuries). Overall 28% were female ( n = 146) and 72% were male ( n = 367). The mean age was 20.5 years. Assault-injured patients of both genders were more likely than controls to give a 30-day history of drinking any alcohol (OR 6.3) and binge drinking (OR 6.7). They were also more likely to report any physical fight (OR 4.4) or any physical fight requiring medical care in the past 6 months (OR 5.08), and lifetime history of arrest (OR 5.1) or conviction (OR 6.7). Drugs and/or alcohol were used by victims prior to 78% of the assaults. Significant differences were not detected between females (76%) and males (79%). Overall, 47% of assault-injured youth and 15% of controls reported a history of a fight requiring medical treatment in the past 6 months. Discussion: Violence is a chronic and recurring disease, suggesting opportunities for interventions during health care contacts. Our population of assault-injured youth demonstrated significant rates of alcohol use and binge drinking, as well as alcohol use prior to the assault. Future secondary violence prevention initiatives should consider targeting alcohol use and abuse.